Frequency of complications at shaft fractures according to kharkiv traumatological medical-social expert committee (MSЕC) data - Popsuishapka, Olexii; Litvishko, Kharkiv Medical Academy of Postgraduate Education. Ukraine MD, Prof. in Traumatology and Orthopaedics; Uzhegova, Olga; Pidgaiska, Olga (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
Objective: to determine the incidence of complications after treatment of shaft fractures according to the inter-regional Specialized Traumatological Medical and Social Expert Commission in Kharkiv and Kharkiv region. Methods: we studied the incidence of nonunions, osteomyelitis, radial nerve neuropathy in 773 patients with shaft fracture of the extremities, who underwent primary examination at the MSEC for the period 01.01.2016–31.12.2018. Among them, 96 % were patients of preretirement age. There were 461 patients with tibia fractures, forearm — 49, femur — 173, humerus — 90. The frequency of nonunion in subgroups is analyzed depending on the method of fragments fixation. Results: after bone fragments osteosynthesis at isolated tibia fractures nonunion was found in 11.9 % of cases, at intramedullary blocking nail — 16.0 %, external rod fixators — 3.0 %, Ilizarov fixator — 18.4 %, plaster cast bracing — 7.6 %. After treatment of femur fracture with plate osteosynthesis, nonunion was found in 9.4 %, after intramedullary nailing — in 12.8 %. At humerus fractures and forearm fractures which were treated with plate osteosynthesis, nonunion was recorded in 19.0 and 28.6 % of patients respectively, and radial nerve neuropathy – was observed in 25.0 and 26.4 %. The incidence of osteomyelitis at internal osteosynthesis was 2.9– 7.7 %. Conclusions: osteosynthesis was used in 36.6 % of cases of tibia shaft fractures and was the most common used method of fragments fixation in isolated shaft fractures: 64.9 % — femur; 75.6 % — humerus; 100.0 % — forearm bone fragments. The second most frequent method of fixation was intramedullary nailing osteosynthesis. The main complication of treatment was fragments nonunion, and in the case of plate osteosynthesis at humerus and forearm fractures was radial nerve neuropathy.